2020
DOI: 10.1021/acsnano.0c07206
|View full text |Cite
|
Sign up to set email alerts
|

Wood-Nanotechnology-Based Membrane for the Efficient Purification of Oil-in-Water Emulsions

Abstract: With increasing amounts of oily water discharged from industrial and domestic sources, purifying oily emulsions using effective and eco-friendly methods is of great significance. Although functional membranes with selective wettabilities have been extensively explored for the efficient purification of oil-inwater emulsions, the development of functional membranes that use green and inexpensive materials, are simple to fabricate, and are easy to scale up remains very challenging. Herein, we report a simple appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(57 citation statements)
references
References 57 publications
0
57
0
Order By: Relevance
“…Hwang and co‐workers (2020) proposed a simple top‐down method to prepare a highly porous, flexible and super‐hydrophilic wood separation membrane by removing lignin and hemicellulose from wood. [ 234 ] Due to its superhydrophilicity‐underwater superoleophobicity combined with a microporous structure (less than 10 µm), resulting in good separation performance to emulsifiers stabilized oil‐in‐water emulsions and anti‐oil adhesion capacity. Although this green, low cost, degradable and naturally renewable biomass‐derived membrane, it has shown great potential to replace existing filter media in various industries.…”
Section: Special Wettability Membranes For Oil/water Emulsions Separationmentioning
confidence: 99%
“…Hwang and co‐workers (2020) proposed a simple top‐down method to prepare a highly porous, flexible and super‐hydrophilic wood separation membrane by removing lignin and hemicellulose from wood. [ 234 ] Due to its superhydrophilicity‐underwater superoleophobicity combined with a microporous structure (less than 10 µm), resulting in good separation performance to emulsifiers stabilized oil‐in‐water emulsions and anti‐oil adhesion capacity. Although this green, low cost, degradable and naturally renewable biomass‐derived membrane, it has shown great potential to replace existing filter media in various industries.…”
Section: Special Wettability Membranes For Oil/water Emulsions Separationmentioning
confidence: 99%
“…Carbonization strategies followed by nanoparticle infiltration is used to provide electrical properties for energy-storage applications ( Chen C. et al, 2017 ; Luo et al, 2017 ; Song H. et al, 2018 ; Wang Y. et al, 2018 ; Tang et al, 2018 ; Zhu et al, 2018 ; Peng et al, 2019 ; Garemark et al, 2020 ). Since wood is designed for liquid transport in the tree stem, it can also be functionalized and serve as a membrane for water treatment or oil-water separation purposes ( Chen F. et al, 2017 ; Vidiella del Blanco et al, 2017 ; Fu et al, 2018a ; Guan et al, 2018 ; Vitas et al, 2018 ; Ding et al, 2020 ; Goldhahn et al, 2020 ; Kim et al, 2020 ).…”
Section: Functionalized Wood Composites With Controlled Nanostructurementioning
confidence: 99%
“…Wang et al have reported an interesting method of using gold nanoparticles (enriched by expanded genetic alphabet transcriptions) to increase the effectiveness of detecting the large natural or artificially synthesized RNAs through an RNA nano-based labeling Nanomaterials can be utilized in the form of membranes. Chemically or physically synthesized nanomembranes remarkably advance the conventional water purification techniques (Lohrasebi and Koslowski 2019;Kim et al 2020). Incorporating nanomembranes with bioreactors is the basis of the membrane bioreactor (MBR) technique, which is exploited in wastewater reclamation (Ma et al 2018).…”
Section: Introductionmentioning
confidence: 99%